AE-02 Veterinary Anatomy and Histology Approach for High School Biology Lesson of Brawijaya Smart School (BSS) as Initial Veterinary Education - Fajar S. Permata; Analis W. Wardhana; Herlina Pratiwi; Dyah A.O.A. Pratama; Agung P.W. Mahendra (Media Veteriner, 2015)
Veterinary Anatomy and Histology Approach for High School Biology Lesson of Brawijaya Smart School (BSS) as Initial Veterinary Education